Reuse of ceramic sanitary waste as an aggregate in concrete resistant to high temperature - Halicka, Anna; Ogrodnik, Paweł; Zegardło, Bartosz (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
In this paper the studies on reuse of ceramic sanitary ware wastes as aggregate in the concrete resistant to high temperatures are presented. Concrete specimens containing alumina cement and crushed sanitary ceramic wastes as an aggregate were heated in 1000oC. It was found that after heating, these specimens preserved their shape and cohesion, and showed no cracks and defects. In contrast, specimens of concrete with alumina cement and traditional aggregate (granite and gravel) after heating were cracked and damaged. Despite some decrease in strength after heating, specimens with sanitary ceramic wastes continued to display high compressive strength and tensile strength.